Studies on residual strength characteristics of slurry-infiltrated fibrous concrete - Bhashya, V.; Kumar, S. Sundar; Ramesh, G.; Bharatkumar, B.H.; Krishnamoorthy, T.S. (Journal of Structural Engineering, 2024)
In order to use steel fiber reinforced concrete (SFRC) in structural application, certain characteristic material properties that could be adopted in design procedures need to be determined. This study has determined the flexural and Residual- Strength of Steel Fiber-Reinforced Concrete with various volumes of fibres and the results have been compared with similar parameters of slurry-infiltrated fibrous concrete (SIFCON). Residual strength parameters determined using ASTM C 1609, ASTM C 1018, ASTM C 1399 are presented. It was observed that average residual strength of SFRC increased as the fiber volume increases. The residual strength of specimens partially replaced with SIFCON was found to be relatively very high.